Product archaeology for identifying an impact in society and technology - Lee, Edwin Wei Jie (2019)
Technological advancement during the 20th centuary have been tremandous. However, the greatest technological advance of the 20th century can be observed in the field of aerospace. Before 1903, the idea of flight is just an idea, a dream. It wasn’t until the Wright brothers and Glenn curtiss redefined the principles of flight that the possibility of flight starts to slowly become a reality. This report will study this young and blooming industry, its impact based on the four factors of product archeaology namely global, economical, environmental and societal as well as the steps taken by the United Nations to address the pollution caused by it. An introduction of Kolb’s four stage learning process and its relation to the archaeology process will be addressed. Kolb’s four stage learning process will be used to guide the “archaeology” process. During the discussion phase, 16 points categorized by the four stage of archaeology and further subcategorized into the four factors of product archaeology will be discussed based on research, facts and unbaised opinion. A conclusion will be drawn by weighing the points presented throughout the archaeology process.